Capital structure, agency cost, size and firm value of small and medium listed companies - Gusni; Merdekawati, Siska; Jatnika, Fitri Pratiwi; Agustia, Widi Nurina; Marina, Lastri; Anisa, Risna (CENTRAL ASIA AND THE CAUCASUS, 2022)
Firm value has an important role because it can explain how the market appreciates the company. This paper aims to explore the influence of capital structure, agency cost, and firm size on the company value of small and medium-listed firms in the Indonesian stock exchange. In the way to achieve the study objective, data was gathered from 227 small and medium listed firms from 2019 to 2020 selected by using certain criteria. This study applied a panel data regression model with a random effect approach to detect the impact of capital structure, agency cost, and firm size on the firm value. Statistical test results denote that capital structure and agency costs have a positive effect on firm value, while firm size has no effect. These study findings provide an outlook that capital structure decisions and agency cost control can maximize firm value in small and medium companies listed on the development index of the Indonesian capital market.